Community’s pride of Belanja Sedap Mart - Mhd Sarif, Suhaimi; Abdul Razak, Dzuljastri; Zainudin, Dolhadi; Yahya, Rohaziah (IIUM Press, 2026)
This case explores the entrepreneurial journey of Jamil, a former army staff sergeant, who transforms a modest neighbourhood minimarket into a community anchor that supports local food security. Jamil leverages his military values of discipline, perseverance, and service to overcome financial hardship, narrow margins, and evolving retail competition by diversifying into side businesses and adapting to changing consumer trends. His story highlights leadership through humility, innovation in micro-business operations, and profound community engagement. The case offers rich insights for understanding veteran entrepreneurship, small businesses' resilience, and the social role of neighbourhood stores in sustaining community well-being